Robust disturbance rejection control of grid-connected fuel cell converters with grid support ability under unbalanced faults - Sabir, Adeel; Ibrir, Salim (Energy systems (Berlin. Periodical), 2020)
This work proposes a high-performance, robust and low-complexity control strategy for grid-connected fuel cell converters that operate under several performance limiting conditions such as grid faults, parametric and modeling uncertainties, unknown disturbances, step changes and noise. The strategy enables the fuel cell-based distributed generators to ride through balanced and unbalanced grid faults and fulfills the modern grid code requirements that mandate them to actively support the grid in case of contingencies. The controller is built by combining disturbance rejection control and repetitive control, both having simple structures and attractive performance features. Moreover, during grid faults, the strategy manages to keep the active power delivered to the grid constant and the phase currents sinusoidal, without a phase locked loop or the positive and negative sequence components of the unbalanced grid voltages or currents. As a result, the controller’s computational and structural complexity are reduced without compromising its performance. Several test cases are run using the SimPowerSystems TM toolbox of MATLAB/Simulink computing environment to demonstrate the response of the proposed strategy and ascertain its performance under grid faults, parametric uncertainties, noise and unknown disturbances.